Triple Elimination Data Analysis (HIV, Syphilis, and Hepatitis B) among Pregnant Women in Denpasar City, Bali - Desak Nyoman Widyanthini; Desak Made Widyanthari; Ni Made Dian Kurniasari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2026)
Background: In 2017, the Ministry of Health of the Republic of Indonesia launched the 'Triple Elimination' initiative, aiming to eradicate the transmission of syphilis, hepatitis B, and HIV from mother to child. This article presents the results of analysing data from the HIV/AIDS and STI Information System (SIHA) and the Hepatitis and Gastrointestinal Infection Information System (SIHEPI) among pregnant women tested for HIV, syphilis, and hepatitis B in Denpasar City, Bali.Methods: A descriptive study with a cross-sectional design was conducted at two community health centres in Denpasar City, using secondary data from SIHA and SIHEPI collected between 2020 and 2022. Data were analysed using univariate and bivariate analyses, with the chi-square test.Result: According to SIHA reports, 3,831 pregnant women were tested for HIV, with a positivity rate of 0.2% (95% CI: 0.09%-0.4%); 3,716 were tested for syphilis, with a positivity rate of 0.9% (95% CI: 0.7%-1.3%); and 4,503 were tested for hepatitis B, with a positivity rate of 1.4% (95% CI: 1.1%-1.8%). Data analysis revealed a significant correlation between HIV test results and the level of education (p<0.001). Syphilis was significantly associated with certain risk factors (p<0.001), while maternal age was significantly associated with hepatitis B infection (p=0.030).Conclusion: Although the prevalence of HIV, syphilis, and hepatitis B among pregnant women in Denpasar City is relatively low, early screening and enhanced integration of triple elimination efforts across healthcare settings remain essential.